The engineering design of systems : - Buede, Dennis M. (John Wiley & Sons, 2009)
The Engineering Design of Systems, Second Edition compiles a wealth of information from diverse sources to provide a unique, one-stop reference to current methods for systems engineering. It takes a model-based approach to key systems engineering design activities and introduces methods and models used in the real world.